Analisis Produksi Beras di Indonesia - Lim Sanny (Bina Nusantara University, 2010)
Most of Indonesian still needs rice as a staple food. More and more quantity of people in a region will be increasing amount consumption of food in region, while decrease of rice field area that become different to public building or industrial affairs and economic transformation from agrarian affairs to nonagrarian affairs will be consequence rice production descend. Until now, domestic rice production was not able to meet its growing demand, so that Indonesia remains dependent upon rice import. This condition was made worse by conversion of fertile lowland in Java. Therefore, rice production growth was leveling-off. In the future, there should be some efforts to increase rice production, although land conversion is still going on. This study is aimed to assess the performance of lowland use, its contribution and prospect to increase rice production. The results showed that lowland is the main source of rice production. Another potential is improvement of intensification through promotion of intensification with integrated crops management. The implementation of these strategic policies should be supported by development and renovation of infrastructures as well as establishment of credit scheme to enable farmers to adopt modern technology.